2021
DOI: 10.51847/5lslf8cpox
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about breast cancer risk factor and breast self-examination among female students at Taif university

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The investigations on breast cancer in 47 countries from 1987 to 2013 show that eh mortality rate due to breast cancer has been reduced in the last decades in 39 countries out of these countries due to advancements in diagnosis and treatment of this disease (Eid MM, et. al., 2021;Algarni SB, et.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations on breast cancer in 47 countries from 1987 to 2013 show that eh mortality rate due to breast cancer has been reduced in the last decades in 39 countries out of these countries due to advancements in diagnosis and treatment of this disease (Eid MM, et. al., 2021;Algarni SB, et.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cancer-related diseases is on the rise throughout the globe [1,2]. In 2020, the International Agency for Research on Cancer (IARC) reported an estimated 19.3 million cases of cancer worldwide and 10 million fatalities therein [3].…”
Section: Introductionmentioning
confidence: 99%
“…About half of all breast cancer cases and 60% of all cancer deaths are thought to occur in economically developing nations. [1] Breast cancer is the most often diagnosed type of cancer. [2] Breast cancer incidence rates have been rising in many African and Asian nations while declining in some western countries since 2000.…”
Section: Introductionmentioning
confidence: 99%